2018
DOI: 10.1029/2018ja025874
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Escape of Spacecraft Photoelectrons Caused by Langmuir and Upper Hybrid Waves

Abstract: The spacecraft potential is often used to infer rapid changes in the thermal plasma density. The variations in spacecraft potential associated with large‐amplitude Langmuir and upper hybrid waves are investigated with the Magnetospheric Multiscale (MMS) mission. When large‐amplitude Langmuir and upper hybrid waves are observed, the spacecraft potential increases. The changes in spacecraft potential are shown to be due to enhanced photoelectron escape from the spacecraft when the wave electric fields reach larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 20 publications
(51 citation statements)
references
References 33 publications
4
47
0
Order By: Relevance
“…This could cause more or fewer electrons to escape the potential well of the spacecraft (e.g., Malaspina et al, 2014;Wang, Malaspina, Hsu, et al, 2014). Numerical simulations by Graham, Vaivads, Khotyaintsev, Eriksson, et al (2018) and a combination of numerical simulation and laboratory experiments (Wang, Malaspina, Hsu, et al, 2014) found that this effect becomes important for very large magnetic fields B ∼ 10 3 nT which are much larger than the typical magnetic fields at the magnetopause. Effectively, the larger magnetic field causes the electron gyroradius to be smaller.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This could cause more or fewer electrons to escape the potential well of the spacecraft (e.g., Malaspina et al, 2014;Wang, Malaspina, Hsu, et al, 2014). Numerical simulations by Graham, Vaivads, Khotyaintsev, Eriksson, et al (2018) and a combination of numerical simulation and laboratory experiments (Wang, Malaspina, Hsu, et al, 2014) found that this effect becomes important for very large magnetic fields B ∼ 10 3 nT which are much larger than the typical magnetic fields at the magnetopause. Effectively, the larger magnetic field causes the electron gyroradius to be smaller.…”
Section: Discussionmentioning
confidence: 99%
“…In the work of Torkar et al (2017) and Graham, Vaivads, Khotyaintsev, Eriksson, et al (2018), a clear effect of the electric field on the spacecraft potential was demonstrated, causing enhanced photoelectron escape from the spacecraft. This can lead to inaccuracies in determining the electron number density from the spacecraft potential.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations